Medicinal plants and rituals. Magicotherapeutic and magicoprophylactic plant uses in Pallars (Pyrenees, Catalonia, Iberian Peninsula) - Antoni Agelet; Joan Vallès (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
Medicinal plants and rituals.Magicotherapeutic and magicoprophylactic plant uses in Pallars (Pyrenees, Catalonia, Iberian Peninsula)